Liability of launching state on space tourism - Mulyana, Septira Putri; Raodah, Putri (Ex Aequo Et Bono Journal Of Law, 2023)
Current use of space as one of the economic factors supporting the country’s economic has experienced a very significant increase. The Treaty Principles Governing the Activities of States in the Exploration and Use of Outer Space, Including the Moon and Other Celestial Bodies (Outer Space Treaty 1967) stipulate that every activity carried out in space must be in accordance with the United Nations charter and must always maintain peace and security. one of the developing commercial activities is space tourism. This research is a normative legal research with a statutory and conceptual approach. The technique of gathering legal material is carried out by reviewing related literature and analyzing various legal references relevant to the problem under study for further analysis qualitatively and descriptively. This article will examine in depth related to whether the existing space law conventions are still relevant to regulating space tourism activities nowadays? And how the launcher state liability in the event of space tourism accidents?. This article conclude that some  the existing space law conventions are still relevant to regulating space tourism activities nowadays. And the launcher state liability are divided into two aspects. Based on liability convention and warswa convention. This is because space tourism activity use two types of aerospace.